The current malaria morbidity and mortality in different transmission settings in Western Kenya. - Anthony Kapesa (PLoS ONE, 2018)
BACKGROUND:Passive surveillance of malaria in health facilities remains vital for implementation of control and elimination programs. It is therefore essential understanding current age profile of clinical malaria morbidity, mortality and presentations in areas with variant infection susceptibility. This study aimed at understanding the current malaria morbidity and mortality in Western Kenya. METHODS:Surveillance of clinical and asymptomatic parasitological positivity rates of all malaria suspected patients and school children were respectively determined from June 2015 to August 2016. From 2014 to 2016, register books in hospitals were referred and the confirmed malaria cases in conjunction with total number of monthly outpatient visits (OPD) counted. All registered malaria admissions were counted together with other causes of admissions. Moreover, outcome of malaria admissions in terms of discharge or death was recorded using inpatient charts within the same time frame. Prospective surveillance of severe malaria collected information on clinical features of the disease. Giemsa stained blood slides confirmed existence of malaria parasitemia. Chi-square and analysis of variance tests were used, respectively, to compute proportions and means; then a comparison was made between different age groups, periods, and study areas. RESULTS:During the survey of asymptomatic infections among school children, overall blood slide positivity ranged from 6.4% at the epidemic prone site to 38.3% at the hyperendemic site. During the clinical malaria survey, school age children (5-14) presented with overall the highest (45%) blood slide positivity rate among those suspected to have the infection at the epidemic prone study site. The survey of all malaria confirmed and registered cases at OPD found 17% to 27% of all consultations among <5 children and 9.9% to 20.7% of all OPD visits among the ≥5 patients were due to malaria. Moreover, survey of all registered causes of admission in hospitals found 47% of admissions were due to malaria. The disease was a major cause of admission in epidemic prone setting where 63.4% of the <5 children and 62.8% of the ≥5 patients were admitted due to malaria (p>0.05) and 40% of all malaria admissions were school age children. Malaria related death rate was highest among <5 years at the hyperendemic site, that is 60.9 death per 1000 malaria <5 admissions. Conversely, the epidemic prone setting experienced highest malaria related death among ≥15 years (18.6 death per 1000 admissions) than the < 15 years (5.7 death per 1000 admissions of the <15 years) (p< 0.001). Surveillance of severe form of the disease found that hyperpyrexia, hyperparastemia, prostration and convulsions as common presentations of severe disease. CONCLUSION:Malaria is still the major cause of hospital consultations in Western Kenya with an alarming number of severe forms of the disease among the school aged children at the epidemic prone setting. Mortalities were higher among <5 children years in high infection transmission setting and among ≥15 years in low and moderate transmission settings. Surveillance of asymptomatic and symptomatic malaria along with evaluation of current interventions in different age groups should be implemented in Kenya.